2005
DOI: 10.1103/physrevlett.95.035005
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Interchange Modes in Mirror Plasmas by a Nonlinear rf-Plasma Wave Coupling Process

Abstract: Experimental and theoretical studies are made of the consequences of a nonlinear coupling process between pump rf waves and interchange modes in mirror plasmas. It is demonstrated that the interchange-stable operation window exists depending on the applied rf power and gamma=omega(0)/Omega(i), where omega(0) (Omega(i)) is the angular frequency of the applied rf wave (ion cyclotron frequency). Results are shown that the nonlinear wave coupling process gives rise to the operation window near the resonance (gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…There was a probe array on each end of Hanbit with four probes so arranged that there were two probes on a field line 90 • apart in four azimuthal locations, the same system as used in previous studies on Hanbit by Jhang et al [3] and Yoon et al [19]. The same checks were made as for those experiments.…”
Section: Probe Data Analysis For the Divertor Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a probe array on each end of Hanbit with four probes so arranged that there were two probes on a field line 90 • apart in four azimuthal locations, the same system as used in previous studies on Hanbit by Jhang et al [3] and Yoon et al [19]. The same checks were made as for those experiments.…”
Section: Probe Data Analysis For the Divertor Experimentsmentioning
confidence: 99%
“…Hanbit [1] is about half of the original TARA [2] tandem mirror device from MIT. Earlier work in Hanbit [3] showed that it was possible to stabilize the m = −1 flute type MHD instability with RF power near the cyclotron resonance by the sideband coupling process. We undertook investigations to see whether the m = −1 MHD flute-like instability could be stabilized by a mirror divertor [4][5][6][7] and the kinetic stabilizer (KS) of Post et al [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Generation or injection of strong waves into mirror machines results in a strong wave-particle interaction. In this case, the excitation of sideband waves induced by particle trapping is observed in laboratory experiments [47,48]. Potentially, the effects considered in our study can explain formation of such secondary (sideband) wave emissions.…”
Section: Discussionmentioning
confidence: 59%
“…Appearance of accelerated particle populations in the Free-Electron Laser experiments with Variable Parameter Wigglers [99,100] is described by essentially the same equations as trapping into the cyclotron resonance with electromagnetic waves. Generation or injection of strong waves into mirror machines result in a strong wave-particle interaction and excitation of sideband waves induced by particle trapping [e.g., 101,102]. Electron surface acceleration in the ultraintense laser pulse experiments represents a classical example of electron trapping into the Cherenkov resonance [103].…”
Section: Space and Laboratory Plasma Systems With Resonant Wave-partimentioning
confidence: 99%